A Proposed Fragility Curve Based on PO-ID Hybrid Analysis for Seismic Assessment Performance of the Reinforced Concrete Continuous Bridges in Earthquake Prone Area - Khin Thuzar Htay; Jafril Tanjung; Masrilayanti; Monita Olivia; Fadzli Mohamed Nazri; Mulyadi Bur (Buildings)
In earthquake-prone regions, the seismic performance assessment of reinforced concrete (RC) continuous bridges is critical for ensuring their resilience and safety. This study proposes a fragility curve developed through a hybrid pushover–incremental dynamic (PO-ID) analysis to accurately evaluate the seismic vulnerability of RC continuous bridges. The proposed method integrates the advantages of pushover analysis, which provides insights into the bridge’s capacity, with incremental dynamic analysis, which captures the bridge’s response under varying earthquake intensities. The resulting fragility curves offer a more comprehensive understanding of the likelihood of bridge failure at different seismic intensities. Incremental dynamic analysis (IDA) effectively illustrates a bridge’s response to increasing seismic demands but does not account for ultimate displacement under static lateral loads. Pushover analysis (POA) is useful for capturing maximum displacement capacity under static forces, yet it falls short of addressing the dynamic effects of near-fault ground motions. The hybrid approach combines the strengths of both IDA and POA, and this hybrid method’s heightened sensitivity to damage states allows for earlier detection and conservative displacement estimates, improving seismic assessments, informing design and retrofitting practices, and enhancing safety by addressing transverse displacements and weak axis vulnerabilities.